The relationship between high ratios of CD4/FOXP3 and CD8/CD163 and the improved survivability of metastatic triple-negative breast cancer patients: a multicenter cohort study - Jeffry Beta Tenggara; Andhika Rachman; Joedo Prihartono; Lisnawati Rachmadi; Sonar Soni Panigoro; Didik Setyo Heriyanto; Noorwati Sutandyo; Intan Russianna Nasution; Familia Bella Rahadiati; Ricci Steven; Rachelle Betsy; Samuel Juanputra; et al. (BMC Research Notes, 2024)
Abstract Background Triple-negative breast cancer (TNBC) has been documented as the most aggressive subtype of breast cancer. This study aimed to analyze antitumor and protumor immune activities, and their ratios as significant prognostic biomarkers in metastatic TNBC (mTNBC). Methods A multicenter cohort study was conducted among 103 de novo mTNBC patients. The expression of CD8 and CD163 was evaluated using immunohistochemistry staining, CD4 and FOXP3 using double-staining immunohistochemistry, and PD-L1 using immunohistochemistry and RT-PCR. Results Multivariate analysis revealed that high CD4/FOXP3 (HR 1.857; 95% CI 1.049–3.288; p = 0.034) and the CD8/CD163 ratio (HR 2.089; 95% CI 1.174–3.717; p = 0.012) yield significantly improved 1 year overall survival (OS). Kaplan–Meier analysis showed that high levels of CD4 (p = 0.023), CD8 (p = 0.043), CD4/FOXP3 (p = 0.016), CD8/FOXP3 (p = 0.005), CD8/CD163 (p = 0.005) ratios were significantly associated with higher rate of 1 year OS. Furthermore, 1 year OS was directly correlated with antitumor CD4 (R = 0.233; p = 0.018) and CD8 (R = 0.219; p = 0.026) and was indirectly correlated with protumor CD163 and FOXP3 through CD4/FOXP3 (R = 0.282; p = 0.006), CD4/CD163 (R = 0.239; p = 0.015), CD8/FOXP3 (R = 0.260; p = 0.008), and CD8/CD163 (R = 0.258; p = 0.009). Conclusion This is the first study to demonstrate that high levels of CD4/FOXP3 and CD8/CD163 significantly improved the 1 year OS in de novo mTNBC patients. Thus, we recommend the application of these markers as prognosis determination and individual treatment decision.